Mapping Green Accounting Research Trends in Indonesia : A Systematic Literatur Review Perspective from 2017 to 2024 - Erstiawan, Martinus (Universitas Nahdlatul Ulama Sidoarjo, 2024)
Research Objective: This study examines the contribution of research to the development of green accounting, both theoretically and practically, and offers recommendations for future research based on a literature mapping. The literature review method was used, employing Harzing’s Publish or Perish (Window GUI Edition 8) application with Google Scholar as the source, using the keyword